Conformal Array Pattern Synthesis and Activated Elements Selection Strategy Based on PSOGSA Algorithm - Bin Sun; Chunheng Liu; Yang Liu; Xiaofang Wu; Yongzhen Li; Xuesong Wang (International Journal of Antennas and Propagation)
The pattern synthesis and activated element selection for conformal array is investigated based on hybrid particle swarm optimization-gravitational search algorithm (PSOGSA) in this paper. With the introduction of PSOGSA algorithm which is a novel hybrid optimization technique, the element excitations are optimized to obtain the desired pattern for conformal array in the case of considering uncoupled and coupled element pattern. Numerical simulation and full-wave electromagnetic calculation verify the advantage and efficiency of our method. Then, a novel strategy of activated element selection based on PSOGSA algorithm is proposed for saving the energy consumption in conformal array.